Three new species of Sinacroneuria Yang & Yang, 1995 (Plecoptera: Perlidae) from Zhejiang Province, southeastern China - Xiang, Ya-Nan; Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2022)
Three new species of Sinacroneuria Yang & Yang, 1995, Sinacroneuria parallela Xiang & Du, sp. nov., Sinacroneuria complana Xiang & Du, sp. nov. and Sinacroneuria longiprojecta Du & Huo sp. nov., from Zhejiang Province of southeastern China are described and illustrated. A list and provisional key to Sinacroneuria males of Zhejiang Province are also presented.